Autobiographical recall of mastery experiences is a mechanism of self-affirming under social identity threat. Issue 1 (2nd January 2020) - Tavitian-Elmadjian, Lucy; Bender, Michael; Van de Vijver, Fons J. R.; Chasiotis, Athanasios; Harb, Charles
ABSTRACT: Autobiographical memories are relevant to many areas of psychological functioning. So far, however, there is no evidence whether personal memories can also be instrumental for self-affirmation. We conducted two experiments, varying national identity threat among U.S. Americans recruited through MTurk. In Study 1, participants spontaneously recalled autobiographical memories after being exposed to varying levels of threat. When the threat was identity-relevant, those who spontaneously recalled mastery autobiographical memories had higher collective self-esteem than those who did not. In Study 2, we instructed participants to recall either mastery autobiographical memories or routine memories. When the threat was identity-relevant, collective self-esteem was again higher for mastery recall compared to routine recall, moderated by national identification and self-esteem. We also found a general, self-affirmative effect of autobiographical memories, regardless of threat relevance or recall content. Findings provide a first empirical demonstration that autobiographical recall can enhance self-affirmation in identity threat situations.